The Influence of Brand Image, Price, and Promotion on Purchase Decisions for Jiniso - Purnamawati, Ida Ayu Putu Santi; Maharani, Ni Made Dinda Dwi; Putri, Sukmasari Triana Gita (International Journal of Environmental, Sustainability, and Social Science, 2026)
Consumer purchase decisions for Jiniso products are not completely stable, as different shopping experiences can influence their level of satisfaction and future repurchase intentions. Purchase decisions are influenced by many factors, such as brand image, price, and promotion. The research problem in this study is how brand image, price, and promotion influence purchase decisions for Jiniso fashion products on the e-commerce platform Shopee in Denpasar. This study aims to determine the influence of brand image, price, and promotion on purchase decisions. The population in this study was Jiniso fashion product consumers in Denpasar City, a sample of 85 respondents. The research method used was quantitative. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, F-Test, and t-Test using SPSS version 26. The results showed that brand image, price, and promotion had a positive and significant influence on purchase decisions. Brand image had a positive and significant influence on purchase decisions, price had a positive and significant influence on purchase decisions, and promotion had a positive and significant influence on purchase decisions. The researcher's recommendations include providing honest information about product ingredients, creating promotional policies that are more aligned with product quality, increasing the intensity of promotions on Shopee and striving to provide quality products, aligning promotions with benefits, and implementing attractive promotions.